To sanctify the name of God: ritual precision and martyrdom in Rabbi Ephraim Oshry's Holocaust responsa. Issue 1 (2nd January 2016) - Stern, Nehemia
ABSTRACT: This article will analyze a collection of religious queries and responses written by Rabbi Ephraim Oshry, a well-known halakhic decisor of the Kovno Ghetto. It will demonstrate how Rabbi Oshry utilized questions concerning ritual practice and precision to empirically quantify and categorize a new reality of genocide. Here classical forms of Jewish martyrdom were used as a framework through which ghetto inmates could exert a certain amount of ritualized control over a genocide whose scale was difficult to comprehend, and whose extent they could not predict. Rabbi Oshry's text also demonstrates some of the tragic limitations of ritual activity to act as either an explanatory or efficacious model for confronting the Nazi genocide.